Analisis Optimalisasi Jumlah Parking Stand Dalam Mencapai On Time Performance (OTP) Penerbangan Di Bandar Udara Internasional Husein Sastranegara Bandung - Rossy Nur Intan Damayanti; Kifni Yudianto (Transformasi: Journal of Economics and Business Management, 2024)
Air transportation is any activity that uses aircraft to transport passengers or goods or cargo for one or more airport trips that is time efficient and more effective, and still prioritizes safety to this day. On time performance has a very important influence in the world of aviation. This research uses descriptive qualitative research methods, sources those interviewed were members of Apron Movement Control. The results of this research show that the number of parking stands to achieve on time performance (OTP) at Husein Sastranegara Bandung International Airport has been fulfilled. Apron Movement Control (AMC) officers in optimizing the number of parking stands to achieve On Time Performance (OTP) for flights at Husein Sastranegara Bandung International Airport optimize the use of parking stands that can be used, First Come First Service, Good Communication and Coordination with units related, and Placing the aircraft parking position not too close to the terminal (Remote Stand).